FORMULATION AND IN VITRO EVALUATION OF METOPROLOL SUCCINATE FLOATING TABLETS - Sunil Thakral; Gagan Deep Singh; Neetu Kansal; Amarjit Singh (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2013)
Gastroretentive dosage forms extend significantly the period of time over which the drug may be released. This prolonged gastric retention improves bioavailability, decrease drug waste and improve solubility of drugs that are less soluble in a high pH environment due to their availability in gastric pH for longer duration of time.Floating drug delivery systems have a bulk density less than gastric fluids and hence remain buoyant in the stomach. The main objective of the present study was to develop Gastroretentive (GR) controlled release ormulations of Metoprolol to prolong the gastric retention time so that its bioavailability can be improved. The formulations were prepared by using swellable polymers like HPMC K4M, HPMC K15M, HPMC K100M, Guar Gum, Xanthan Gum, Sodium carboxymethyl cellulose and various effervescent compounds, e.g. sodium bicarbonate, and citric acid by the direct compression method. All the formulations were evaluated for different parameters like floating lag time, total floating time, hardness, weight variation, density measurements, drug content and water uptake/swelling index. Dissolution studies were done for all formulations in 0.1N HCl (pH 1.2). Formulations F3, F4 and F10 were found to provide maximum sustained release of metoprolol s uccinate up to 24 h with optimum floating properties.Key words : Controlled release; Gastro retentive; HPMC; Guargum; Xantham gum